2023
DOI: 10.1155/2023/7710980
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Edible Coating Formulation Using Response Surface Methodology for Delaying the Ripening and Preserving Tomato (Solanum lycopersicum) Fruits

Franck Laurins Tchouala Tazo,
Gabriel Kanmegne,
Alain Ngotio Tchinda
et al.

Abstract: Tomato is a climacteric fruit that has a short shelf life under natural conditions. However, some treatments can be applied in order to extend the shelf life and improve the quality of fruits. The present study aimed at formulating a coating solution based on coffee leaf extract, starch, and Gum Arabic in order to extend the postharvest shelf life of tomato. The response surface methodology (RSM) was used to determine the optimal concentrations of the different abovementioned components in the coating, for bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…As a response to high oxidative stress, which is triggered by environmental factors such as exposure to oxygen, the tomatoes exhibited a rapid initial increment in antioxidant activity, indicating a faster ripening process with accelerated respiration rates. 4,71 This high increment in antioxidant activity is not desirable given that it leads to premature softening, color changes, and potential flavor loss. 5 Rapid ripening can shorten the shelf life of tomatoes, making them less desirable for prolonged storage and marketing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a response to high oxidative stress, which is triggered by environmental factors such as exposure to oxygen, the tomatoes exhibited a rapid initial increment in antioxidant activity, indicating a faster ripening process with accelerated respiration rates. 4,71 This high increment in antioxidant activity is not desirable given that it leads to premature softening, color changes, and potential flavor loss. 5 Rapid ripening can shorten the shelf life of tomatoes, making them less desirable for prolonged storage and marketing.…”
Section: Resultsmentioning
confidence: 99%
“…However, the rate of the degradation of chlorophyll ‘a’ and ‘b’ pigments and the synthesis of lycopene and β-carotene were recorded to be significantly ( p < 0.05) higher for the uncoated fruits, followed by the tomatoes coated with formulations 1 (10 g L −1 AS, 0 mL L −1 EO, 5 g L −1 BW), 2 (10 g L −1 AS, 2.5 mL L −1 EO, 5 g L −1 BW), and 3 (10 g L −1 AS, 5 mL L −1 EO, 5 g L −1 BW), implying their elevated ripening as a function of a higher respiration rate and metabolic activity, as discussed by Naeem et al 40 Nevertheless, the tomatoes coated with formulations 6 (15 g L −1 AS, 5 mL L −1 EO, 5 g L −1 BW), 8 (20 g L −1 AS, 2.5 mL L −1 EO, 5 g L −1 BW), and 9 (20 g L −1 AS, 5 mL L −1 EO, 5 g L −1 BW) exhibited significantly ( p < 0.05) delayed rates of production and breakdown of the pigments, which is attributed to the restricted maturation process during storage. 71 Javanmardi et al 79 reported that the temperature range and respiration rate are the major factors that affect the synthesis of lycopene in tomatoes during storage. Furthermore, significantly ( p < 0.05) delayed rates of production and breakdown of pigments in the fruits with formulations 6, 8, and 9 could also be explained by the effects of clove EOs.…”
Section: Resultsmentioning
confidence: 99%